REFORMASI BIROKRASI DALAM PUSARAN POLITIK LOKAL: KAJIAN KEBIJAKAN PENINGKATAN AKUNTABILITAS DAN TRANSPARANSI DI KANTOR BUPATI KABUPATEN LABUHANBATU - Br Tambunan, Emi Ningsi; Muda, Indra (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
This study investigates the intricate relationship between bureaucratic reform efforts, particularly in enhancing accountability and openness, and the dominant local political dynamics within the administrative offices of the Labuhanbatu Regency. Despite the presence of official commitments and policy frameworks supporting sound governance, their practical implementation at the regional level frequently encounters significant obstacles stemming from strong